2018
DOI: 10.5944/openpraxis.10.1.729
|View full text |Cite
|
Sign up to set email alerts
|

Implementation Factors and Faculty Perceptions of Electronic Textbooks on the iPad

Abstract: A federally managed university in the United Arab Emirates implemented a one-to-one iPad program. In an effort to increase access to interactive digital learning resources on the iPads, they next transitioned from paper-based textbooks (pTexts) to electronic textbooks (eTexts) on the iPad for all course delivery formats. The goal of this study was to survey and report on faculty perceptions among three university divisions with the intent of highlighting factors and barriers influencing adoption of iPad-access… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…It is presently well established in the literature that online learning resources have become more widespread than printed textbooks (Karcmer-Klein & Shinas, 2012;Estable, 2018). New technological systems and tools are rapidly spreading in parallel with the development of educational technology and are used to benefit educational activities (Joo, Bong, & Choi, 2000).…”
Section: Discussion and Conclusion Discussionmentioning
confidence: 99%
“…It is presently well established in the literature that online learning resources have become more widespread than printed textbooks (Karcmer-Klein & Shinas, 2012;Estable, 2018). New technological systems and tools are rapidly spreading in parallel with the development of educational technology and are used to benefit educational activities (Joo, Bong, & Choi, 2000).…”
Section: Discussion and Conclusion Discussionmentioning
confidence: 99%
“…reading a word or PDF file on screen) with print reading; however, not much research has been carried out into examining learners reading behaviors and the educational benefits of recent, more flexible visually presented texts (Rha, 2014, p. 51). Rogers-Estable (2018, p. 48) reported that many faculty members commented that if electronic texts (eTexts) are purely PDF files (or glorified PDFs) then there is no advantage in using them with students.…”
Section: Methodsmentioning
confidence: 99%
“…Textbooks of the past were researched and verified before students were exposed to their content, but the Internet has allowed free publication of information, and it is up to the student to determine their veracity and reliability. It has also influenced reading and memory skills as the concentration required to digest a textbook passage is quite different from that of today's tweets and texts (Rogers-Estable, 2018). Reading for pleasure among teens has decreased in favor of reading to meet practical needs, with an increasing amount of all reading being done online over more traditional forms such as books, newspapers and magazines.…”
Section: Social Media As a Social Learning Platformmentioning
confidence: 99%